PENGAPSAHAN: TRANSLATION MODELS, LOCAL LANGUAGE PRESERVATION, AND LANGUAGE ACCULTURATION PROCESSES IN KIAI BOOKS OF COASTAL JAVA - Jaeni, Muhamad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
Pengapsahan model is a translation model that has long been used by Kiai in several traditional pesantren (Islamic boarding schools) on coastal Java. During this time, the conjugation model is only understood as a tool for analyzing text structures, whereas far more than that, there is a variety of Javanese typically used in pesantren having a social role so that the variety of Javanese is still preserved by pesantren communities. This paper examines the model of analyzing the pesantren books. The study will also look at the formulation of Kitabi Javanese language and the reasons why the variety of Javanese of the pesantren that continues to be preserved and maintained by the pesantren community, as well as how the process of conjugation has become a part of the process of acculturation in Javanese and Arabic in the texts of religious books. The results of this study, First; the conjugation model is a special model for Arabic texts created by Islamic boarding school scholars with various analytical tools in it; Second, the variety of languages used in the conjugation of the book is a variety of Javanese of coastal dialects and it has become a corpus of its language which is called Jawa Kitabi (Kitabi Javanese); Third, the process of acculturation of Arabic-Javanese in the tradition of conjugation is characterized by the emergence of the pegon script, the emergence of Javanese translation books with the Arabic structure of fusha, the existence of mixed code phenomena in the writing and translating pesantren books, both mixed codes of Javanese-Arabic, Javanese-Indonesian and mixed codes of Javanese Krama-Ngoko.